Republic of Slovenia : Financial System Stability Assessment Update, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Insurance Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents a Financial System Stability Assessment Update for Slovenia, including Reports on the Observance of Standards and Codes on Banking Supervision and Insurance Supervision. The Slovenian financial system appears sound overall but faces new challenges and risks with European Union (EU) accession and entry into the new Exchange Rate Mechanism (ERM2). These include increased competitive pressures on Slovenian banks from EU banks, and the risk to bank-asset quality from rapid credit growth triggered by very low real interest rates associated with interest rate convergence in ERM2.